(untitled) (EU and comparative law issues and challenges series (ECLIC), 2023)
This article illustrates in an anecdotal way the impact of digitalisation on international family law. Specifically, it explores the part that digital technologies have played in the expansion of cross-border assisted reproduction, with a particular focus on cross-border surrogacy arrangements. It then examines the interface between international parental child abduction and facial recognition technologies. The EU approach to the use of AI-powered facial recognition technologies is explained, before considering the potential utility of facial recognition technologies in the specific context of international parental child abduction.